The recent advances in the approach of artificial intelligence (AI) towards drug discovery - Khan, Mahroza Kanwal; Raza, Mohsin; Shahbaz, Muhammad; Hussain, Iftikhar; Khan, Muhammad Farooq; Xie, Zhongjian; Shah, Syed Shoaib Ahmad; Tareen, Ayesha Khan; Bashir, Zoobia; Khan, Karim (Frontiers in Chemistry, 2024)
Artificial intelligence (AI) has recently emerged as a unique developmental influence that is playing an important role in the development of medicine. The AI medium is showing the potential in unprecedented advancements in truth and efficiency. The intersection of AI has the potential to revolutionize drug discovery. However, AI also has limitations and experts should be aware of these data access and ethical issues. The use of AI techniques for drug discovery applications has increased considerably over the past few years, including combinatorial QSAR and QSPR, virtual screening, and denovo drug design. The purpose of this survey is to give a general overview of drug discovery based on artificial intelligence, and associated applications.We also highlighted the gaps present in the traditional method for drug designing. In addition, potential strategies and approaches to overcome current challenges are discussed to address the constraints of AI within this field. We hope that this survey plays a comprehensive role in understanding the potential of AI in drug discovery.